Basal serum levels of immunoglobulins G, A, M, and E in the group of patients with cystic fi brosis at Hospital Infantil Universitario de San José Bogotá DC, in 2014 (2016)
Background: Patients with cystic fi brosis have poor lung function and chronic infections which impair the quality of life and are the leading cause of death. Hypogammaglobulinemia is associated with less severe lung disease; hypergammaglobulinemia with major lung impairment, presumably due to a hyperimmune response. Objective: Determine G, A, M, and E immunoglobulins serum levels in patients diagnosed with cystic fi brosis at Hospital Infantil Universitario de San José de Bogotá in 2014. Material and Methods: Case series of patients diagnosed with cystic fi brosis. Fifty three patients were included. Forty one samples of serum IgG, IgA, IgM, and IgE immunoglobulins were taken from patients without acute infectious disease, and who had not received gamma-globulin therapy or immunosuppressive therapy. Body mass index, lung function, bronchiectasis, and Pseudomonas aeruginosa colonization were assessed. Results: 51.2% of participants were male. The median age was 17.7 years; 58.5% of the patients had a normal BMI; the median FEV1 was 67.9%. The frequency of bronchiectasis was 39%, 31.7% were colonized with Pseudomona aeruginosa. Most of the patients had normal immunoglobulin levels; low levels of IgG were present in less than 5% of the patients. Patients with high IgG had bronchiectasis in 85.7%. High IgA was mainly present in male between 10 and 20 years old, who also had the worst respiratory impairment. They also had a greater colonization for more than three months. Bronchiectasis was found in 85% of the cases and was colonized by Pseudomonas aeruginosa. Conclusion: Increase in immunoglobulins levels correlate with bronchiectasis and inversely with FEV.